Histopathology of Microvascular Anastomosis—Comparison of Patent and Nonpatent Anastomosis: An Experimental Study - Gohil, Dhaval; Mohammed, Nasser; Mahadevan, Anita; Pruthi, Nupur (Indian Journal of Neurosurgery, 2021)
Objective To compare the histopathology of patent and nonpatent microvascular anastomosis using rat femoral artery end-to-end anastomosis model.Materials and Methods In 15 Sprague–Dawley rats, end-to-end anastomosis was performed on the right femoral artery. The classical method was used in four cases and one-way up method in 11 cases. The animals were sacrificed after 2 weeks and the anastomosis was subjected to histopathology. The pathological changes in patent and nonpatent cases were compared.Results The immediate patency rate and delayed patency (after 2 weeks) rate was 86.7% and 66.7%, respectively. The mean follow-up was 3 months. At sacrifice, 5/15 anastomosis were not patent. Marked subintimal thickening was noted in ⅘ (80%) of the nonpatent group, which was absent in the patent group. Severe loss or fibrosis of tunica media and marked adventitial inflammation were noted in all nonpatent cases (5/5, 100%). As much as ⅘ of the nonpatent cases had poor or indeterminate apposition; in contrast, good apposition was seen in 6/10 (60%) of the patent group. The mean clamp time and mean suturing time were significantly longer in the nonpatent group (69.2 minutes and 53.8 minutes, respectively) as compared with the patent group (48.8 minutes and 31.8 minutes, respectively). A single case that was initially nonpatent was found to have recanalized at 6 months.Conclusion Minimal intimal injury and reaction, minimal thinning of tunica media, mild-to-moderate adventitial changes, good apposition, and equidistant sutures were associated with a successful microvascular anastomosis. Short duration of vessel clamping time and suturing comes with experience and dedicated practice in a skills laboratory.
Keywords: histopathology; microvascular anastomosis; patency